Image of an “Enemy” as a Factor of Constructing the Ukrainian National Identity - Kryvda, Nataliia; Storozhuk, Svitlana (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2020)
The article shows that contrary to the fact that constructing the image of an “Enemy” for a long time has been remaining an inseparable element of the strategy of forming a national identity, yet it should be regarded as a rudiment of the national policy of the modern period, since then homogeneous national identity was the only way to gain political independence of a conscious proper cultural cutoff of the community. Meanwhile, in today’s conditions, the formation of a homogeneous national identity is a conflict strategy that can lead to a social split and fragmentation of the state borders. Given this, strategies that are aimed at ensuring a high level of citizens’ loyalty to the political state institutions on the basis of “constitutional”, “territorial”, “regional” and other patriotism seem more fruitful. Under conditions of implementing such a strategy and rational cultural policy aimed at developing a system of super-ethnic values that will be shared by the majority of the population of a certain state, it is possible to overcome the world-view split and save the national identity.